Karakterisasi dan Efektifitas Cangkang Bekicot (Achatina fulica) Sebagai Biosorben dalam Menyerap Logam Berat Fe pada Air Limbah Sintetik - Deasy Amanda Valentine; Azhar Azhar; Mitha Putri Paradila (Jurnal Serambi Engineering, 2021)
The metal remittance in this review is Fe metal, since Fe is one of the metals that is generally contained in water. Whenever devoured water containing Fe that surpasses the limit, it will be awful for wellbeing. The purpose for this research was to portray the biosorbent of snail shell powder and to test the presentation of the biosorbent in the retention of substantial metal iron (Fe). From the aftereffects of the FTIR test, it is assessed that there has been an adjustment of chitin to chitosan. The chitosan spectra acquired showed the presence of a retention band at a wave number of 3066 cm-1 because of the extending vibration of the - Goodness bunch. while for the portrayal utilizing SEM, the molecule size of the biosorbent has different sizes, to be specific with a size scope of 2.16 - 3.44 m to 2.54 - 12.12µm. The development of a coral-like surface is the most definitive factor in the partition of the weighty metal retention interaction of Fe. The computation of the viability esteem showed that the adequacy of snail shell powder in engrossing 10 ppm Fe metal was at a mass of 20 g with a mixing season of 30 minutes, which was 99.2%.